"What can the matter be?" : therapeutic interventions with parents, infants, and young children : the work of the Tavistock Clinic under fives service - Emanuel, Louise, 1953-; Tavistock Clinic; Bradley, Elizabeth, ....-; Rustin, Margaret, ....- (London : Karnac, 2008)
This volume is the result of over twenty years of therapeutic interventions with families within the Tavistock Clinic's Under Fives Service. It describes in detail the process of understanding young children's communications and behaviour and the dynamics of family relationships within the consulting room in a lively, accessible style. It covers common themes in work with young children such as disruptive, angry behaviour, separation and sleep difficulties, and problems in the parent/couple relationship. This book is essential reading for all early years professionals hoping to gain a greater understanding of the technique, observational skills and theory which underlie a psychodynamic approach to work with the under fives.
Includes bibliographical references (p. 273-282) and index.
Keywords: Tavistock Clinic; Child Behavior Disorders -- Therapy; Child Development; Child development; Child rearing; Child, Preschool; Family Therapy; Gedragsstoornissen -- Kinderen; Gezinstherapie; Kleuters; Opvoedingsproblemen; Parents -- Psychology; Preschool children -- Mental health